Fisiologia pós-colheita de sorvetão (Zingiber spectabile Griff.) cultivado no submédio São Francisco - Santos, Maria Herbênia Lima Cruz [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Beehive ginger inflorescences have yellow bracts when they are young, which are ornamental and are specially used in gardening projects and as cut flowers. However, there are crop management and postharvest factors that affect the expansion of the species. So, the objective of this work was to study some physiological postharvest aspect of beehive ginger inflorescences grown in the lower middle São Francisco river basin. Flower stems just harvested were submitted to different treatments (distilled water; 75 mg L-1 of silver nitrate - AgNO3; 1000 mg L-1 of cobalt chloride - CoCl2; 5 mg L-1 de GA3 - Progibb® and 10 mg L-1 of 6-benzylamino purine - BAP), in an environment with controlled temperature and humidity, for 15 days. The longevity was monitored from non-destructive analysis (grading scale, fresh weight, consumption and pH of the preservative solution) as well as destructive ones (peroxidase and polyphenol oxidase activity, total soluble and reducing carbohydrates, phenols, putrescine, spermine and spermidine content). The non-destructive analysis showed that the beehive ginger stems treated with gibberelin and silver nitrate presented a better visual aspect according to the grading scale, the ones treated with AgNO3 absorbed a greater volume of the solution during the experimental period, while the ones treated with silver nitrate and BAP had a greater fresh weight. The smallest variation of the preservative solution pH took place with the treatments containing the plant regulators. The destructive analysis revealed that the inflorescences maintained in preservative solutions with gibberelin and distilled water kept their stocks of total soluble sugars for 3 days longer than the stems submitted to the other treatments. The contents of reducing sugars increased 7 considerably in inflorescences treated with cytokinin. The BAP promoted alterations in the activity of the... (Complete abstract click electronic access below)
Keywords: Plantas - Reguladores - Submédio São Francisco; Enzimas - Regulação - Submédio São Francisco; Fenóis; Poliaminas; Pós-colheita - Submédio São Francisco; Polyamines; Phenols; Enzyme regulation; Plant regulators